The language instinct - Pinker, Steven, 1954- (New York : HarperPerennial, 1995)
An introduction to the science of language, discussing such topics as how languages work, historical linguistics, language acquisition, language change, and language perception.
Originally published: New York : W. Morrow and Co., c1994.
Includes bibliographical references (p. 447-472) and index.
Adult
Keywords: Biolinguistics; Language and languages; Language and languages; Linguistics